Paranapiacaba: Centro Cultural - COUTINHO, Beatriz; CARVALHO, Eduarda Siqueira de; RODRIGUES, Evelyn Vitória Silva; BELLA, Leticia Akemi Moriya (014, 2023)
Centros Culturais são identificados por promover novas perspectivas e oportunidades através da arte. O direito à cultura retratado em tais espaços permite que seus usuários produzam ou simplesmente utilizem-na da maneira que for ansiada, democratizando o acesso à mesma. Entretanto, no distrito de Paranapiacaba, observamos a falta de edificações focadas à cultura local e o grande número de patrimônios tombados na área. Sendo assim, este trabalho propõe desenvolver um projeto de um Centro Cultural na vila de Paranapiacaba com a revitalização de um imóvel tombado. A proposição de um espaço voltado à cultura, sendo ele compatível com as demandas locais em cumprimento à função social e cultural, será desenvolvido na Rua Schnoor, 404 – Paranapiacaba, considerando a história e as peculiaridades do terreno e seus entornos. Trata-se de uma maneira para diminuir a desigualdade social de forma que sejam tratadas atividades de natureza cultural, da ordem da criação, reflexão, fruição, distribuição de bens culturais no distrito, antepondo um espaço acessível, inclusivo e sustentável.

ABSTRACT Cultural Centers are identified for promoting new perspectives and opportunities through art. The right to culture portrayed in such spaces allows its users to produce or simply use it as desired, democratizing access to it. However, in the district of Paranapiacaba, we observe the lack of buildings focused on local culture and the large number of listed heritage sites in the area. Therefore, this work proposes to develop a project for a Cultural Center in the village of Paranapiacaba, mainly preserving the historical-cultural, architectural, technological and environmental heritage of the place. The proposition of a space dedicated to culture, being compatible with local demands in fulfillment of the social and cultural function, will be developed at Rua Schnoor, 404 – Paranapiacaba, considering the history and peculiarities of the land and its surroundings. It is a way to reduce social inequality so that activities of a cultural nature are dealt with, in the order of creation, reflection, fruition, distribution of cultural goods in the district, and placing an accessible, inclusive and sustainable space in front of it.
Keywords: Edificações; História; Cultura; Centros culturais; Infraestrutura